2008
DOI: 10.1007/s10571-008-9333-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Changes of Hyperoxidized Peroxiredoxins in Non-Pyramidal and Polymorphic Cells in the Gerbil Hippocampus During Normal Aging

Abstract: Oxidative stress is one of predisposing factors to age-related neurodegeneration in the brain. In particular, thiol-containing groups are susceptible to oxidative stress, which induces the formation of the disulfide bond and/or hyperoxidized form of thiol-containing proteins. We observed the protein thiol levels in the hippocampal homogenates and also investigated changes in hyperoxidized form of peroxiredoxin (Prx-SO(3)) immunoreactivity and proteins levels in the gerbil hippocampal subregions during normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The hyperoxidation of Prxs may also take place in the brain in response to a variety of oxidative trauma: we recently found that an episode of ischemia, followed by reperfusion, induces strong hyperoxidation of Prxs in the mouse cortex 12. Increased levels of hyperoxidized Prxs have also been observed during normal aging in the gerbil hippocampus 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperoxidation of Prxs may also take place in the brain in response to a variety of oxidative trauma: we recently found that an episode of ischemia, followed by reperfusion, induces strong hyperoxidation of Prxs in the mouse cortex 12. Increased levels of hyperoxidized Prxs have also been observed during normal aging in the gerbil hippocampus 13…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, under increased oxidative stress, Prx-SOH is further oxidized by peroxide to sulfinic (-SO 2 H) acid, causing inactivation of peroxidase activity 11. Prx hyperoxidation to Prx-SO 2 H takes place in neurons undergoing oxidative death in vitro, and is associated with ischemic brain damage in vivo as well as normal aging 12,13. Prx-SO 2 H is not a substrate for the resolving cysteine and cannot be reduced by thioredoxin.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative modifications of Prx enzymes were observed during normal aging, and closely correlated with age. 40 Neuronal overexpression of Prx2 in Drosophila melanogaster was found to attenuate oxidative stress and prolong longevity, suggesting Prx2 may function as an antiaging gene. 41 It has been repeatedly shown that altered expression of Prxs occurs in brain tumors though the exact causal role of Prxs in brain tumorigenesis remains to be established.…”
Section: Protection Against Other Neurological Disorders and Conditionsmentioning
confidence: 99%
“…In mitochondria oxidized Prdx3 increased in aged rat liver compared with that of young adults (28 mo vs 12 mo) while the reduced form remained unchanged [119]. The oxidized form of Prdx in hippocampus was lowest at 12 mo and started to increase thereafter [120, 121]. The age-related accumulation of hyperoxidized Prdx appears to be linked to the increase of oxidant production with aging; however, it may also suggest a less efficient Prdx repairing mechanism in senescent cells.…”
Section: Introductionmentioning
confidence: 99%